Properties of Goal Systems: Consistency, Conflict, and Coherence - Rosencrantz, Holger (Studia logica, 2008)
The paper provides a formal representation of goal systems. The focus is on three properties: consistency, conflict, and coherence. An aim is to attain conceptual clarity of these properties. It is argued that consistency is adequately regarded as a property relative to the decision situation or, more specifically, the set of alternatives that the agent faces. Moreover, as a condition of rationality, consistency is stronger than some writers have claimed. Conflict is adequately regarded as a relation over subsets of a given goal system and should likewise be regarded as relative to the set of alternatives that the agent faces. Coherence is given a probabilistic interpretation, based on a support relation over subsets of goal systems.